Perbandingan Kuat Tekan Plasbut Paving Block pada Perendaman Air Tawar dan Air Laut: Comparison of Compressive Strength of Plasbut Paving Blocks when Immersed in Fresh Water and Sea Water - Listriyana, Ani; Silviyanti, Nurul Amalia; Syaifurridzal, Syaifurridzal (Universitas Jember, 2024)
Abstract Processing plastic waste into paving blocks is reducing the negative impact of waste on the environment. Plastic as adhesive and sand, fiber as filler in plasbut paving blocks. In previous studies, the highest compressive strength was obtained in paving blocks with a composition of 771.6 grams of plastic, 1800.4 grams of sand, and 11 grams of coconut fiber, with the fiber placed in the middle of the mold. It is expected that in the future this plastic paving block can be used in coastal and beach areas both to support educational tourism on the beach. Therefore, this study was designed to see how the effect of immersion in seawater on the compressive strength of plasbut paving blocks. The plastic used is polypropylene, and the same composition as previous studies and the addition of the variable of soaking time with fresh water and seawater, 3, 5, 7, 9, 11, 13, and 15 days. Soaking with fresh water produces the highest average compressive strength in the 3rd immersion variation with a compressive strength value of 9.78 MPa. Meanwhile, immersion in seawater produces the highest average compressive strength in the 9th immersion variation with a compressive strength value of 13.44 MPa. Keywords: Plastic, Fiber, Plasbut Paving block, Compressive Strength Abstrak Pengolahan sampah plastik menjadi paving block menjadi solusi dalam mengurangi dampak buruk sampah bagi lingkungan. Plastik sebagai perekat dan pasir serta serabut sebagai filler dalam plasbut paving block. Pada penelitian sebelumnya, kuat tekan tertinggi di dapatkan pada paving block dengan komposisi 771,6 gram plastik : 1800,4 gram pasir : 11 gram serabut kelapa dengan peletakan serabut di tengah cetakan. Di harapkan ke depannya plasbut paving block ini dapat di gunakan di area pesisir dan pantai baik untuk mendukung wisata edukasi di pantai. Oleh karena itu, penelitian ini di rancang untuk melihat bagaimana pengaruh perendaman dengan air laut terhadap kuat tekan dari plasbut paving block. Plastik yang digunakan adalah jenis polypropilene dan komposisi sama seperti pada penelitian sebelumnya dan penambahan variable variasi waktu perendaman dengan air tawar dan air laut yaitu 3 , 5 , 7 , 9 , 11 , 13 dan 15 hari. Perendaman dengan air tawar menghasilkan kuat tekan rata rata tertinggi pada variasi perendaman 3 hari dengan nilai kuat Tekan 9,78 MPa. Sedangkan Perendaman dengan air laut menghasilkan kuat tekan rata rata tertinggi pada variasi perendaman 9 hari dengan nilai kuat Tekan 13,44 MPa. Kata kunci: Plastik, Serabut, Plasbut Paving block, Kuat Tekan